Phenomena of Transportation to Work Mode Choice, Due to The Increase of Oil Prices in Indonesia: A Case Light Rail Transit Depot Project Office-Jakarta - Kurniawan, Andreas Novi; Rifai, Andri Irfan; Rizal S., Muhammad (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Fluctuations in world oil prices and subsidy reduction programs have increased the price of fuel oil in Indonesia. Such conditions affect the decision on transportation mode choice for everyone, and company employees are no exception. This paper aims to analyze the phenomenon of changes in transportation choices due to fuel increases. The method used is a questionnaire distributed to 100 respondents at the Jabodebek Light Rail Transit (LRT) Depo Project office. Data processing is done by using radar chart analysis with Microsoft Excel tools. The results of this study showed ten variables that had different levels of influence. There are three primary parameters: travel time, punctuality, and travel distance for men; travel distance, number of trips, and travel companions for women. So, the travel time parameter has the most significant influence on transportation mode choices for men, and the travel distance parameter has the most significant influence on transportation mode choices for women.